The Study of Knowledge, Attitude and Practice towards Female Circumcision among Female Patients at O&G Outpatient Department, Hospital Ampang, Selangor, Malaysia - Salleha Khalid; Rafida Hanim Mokhtar; Mohd Shamsir Muhammad Aris; Muhammad Riduan Wan Deraman; Nuurain Amirah Mohd Razi; Suhaila Sanip; Maizatul Azma Masri (Universiti Sains Islam Malaysia, 2024)
Female circumcision in Malaysia involves drawing a drop of blood and causing brief pain by nicking the tip of the clitoris or prepuce with a pen-knife or sharp tools. The objective of this paper is to assess the knowledge, attitude, and practice of female circumcision among patients who attended the outpatient Obstetrics and Gynaecology clinic in Hospital Ampang. A cross-sectional questionnaire study using sequential sampling of patients aged > 18-year-old attending the clinic. 80% (315) thought circumcision was performed mainly for religious reasons. The perceived benefits include control of sexual desire among women 78% (111). Responding to the question -would you circumcise your daughter', 97% (380) said they would. There was no significance correlation between respondents being circumcised and their views on having their daughters circumcised (correlation coefficient, r=0.2693). 94.3% (379) believed that circumcision had no complications. 79% (318) of the respondents chose to have the circumcision between 0-6 months. 73% (293) chose a medical doctor as the preferred person to do the circumcision. 72% (289) of the respondents stated that they did not actually know how circumcision is performed. 63% (62) of the non-Muslims had never heard of female circumcision. Although there is no specific statement in the Al-Quran to validate such a practice, majority performed circumcision based on religious grounds. Cultural influence may play a role in why and how circumcision is performed as the practice varies between communities and countries. A medical doctor is the preferred person to perform circumcision although there is no formal training for such a practice and in some countries, it is illegal. Despite wanting to have their daughters circumcised, only few mothers knew how exactly it is done.